Geranylated 4-Phenylcoumarins Exhibit Anticancer Effects against Human Prostate Cancer Cells through Caspase-Independent Mechanism. - Noor Shahirah Suparji; Gomathi Chan; Hani Sapili; Norhafiza M Arshad; Lionel L A In; Khalijah Awang; Noor Hasima Nagoor (PLoS ONE)
Geranylated 4-phenylcoumarins, DMDP-1 & -2 isolated from Mesua elegans were investigated for anticancer potential against human prostate cancer cells. Treatment with DMDP-1 & -2 resulted in cell death in a time and dose dependent manner in an MTT assay on all cancer cell lines tested with the exception of lung adenocarcinoma cells. DMDP-1 showed highest cytotoxic efficacy in PC-3 cells while DMDP-2 was most potent in DU 145 cells. Flow cytometry indicated that both coumarins were successful to induce programmed cell death after 24 h treatment. Elucidation on the mode-of-action via protein arrays and western blotting demonstrated death induced without any significant expressions of caspases, Bcl-2 family proteins and cleaved PARP, thus suggesting the involvement of caspase-independent pathways. In identifying autophagy, analysis of GFP-LC3 showed increased punctate in PC-3 cells pre-treated with CQ and treated with DMDP-1. In these cells decreased expression of autophagosome protein, p62 and cathepsin B further confirmed autophagy. In contrary, the DU 145 cells pre-treated with CQ and treated with DMDP-2 has reduced GFP-LC3 punctate although the number of cells with obvious GFP-LC3 puncta was significantly increased in the inhibitor-treated cells. The increase level of p62 suggested leakage of cathepsin B into the cytosol to trigger potential downstream death mediators. This correlated with increased expression of cathepsin B and reduced expression after treatment with its inhibitor, CA074. Also auto-degradation of calpain-2 upon treatment with DMDP-1 &-2 and its inhibitor alone, calpeptin compared with the combination treatment, further confirmed involvement of calpain-2 in PC-3 and DU 145 cells. Treatment with DMDP-1 & -2 also showed up-regulation of total and phosphorylated p53 levels in a time dependent manner. Hence, DMDP-1 & -2 showed ability to activate multiple death pathways involving autophagy, lysosomal and endoplasmic reticulum death proteins which could potentially be manipulated to develop anti-cancer therapy in apoptosis resistant cells.